Syntactic Analysis of Movement Transformation in Bahasa Indonesia - Adha, Ruly (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2022)
The objective of this article was to analyse the types of movement transformation which is applied in Bahasa Indonesia. This article aims to collect ideas, theories, and reported empirical data within the context of scholarship in the library. The theory used in this article was taken from the theory of Transformational Generative Grammar (TGG) introduced by Noam Chomsky. This article was an attempt to highlight how Chomsky’s concept called movement transfssormation works in Bahasa Indonesia. The data were taken from some sentences in Bahasa Indonesia. In this article, the sentences were analysed by using IC analysis. IC analysis is a method of analysing sentences by dividing them into their constituent structures. The methods used in analysing sentences were bracketing and tree diagram. Some types of movement transformation that were applied in Bahasa Indonesia were Affix Hopping, Interrogative (Aux Movement), Wh-Movement, Passive Transformation, Dative Movement, Topicalization, Particle Movement, and Relative Movement.